Investigating consumers' and informal carers' views and preferences for consumer directed care: A discrete choice experiment. (September 2015) - Kaambwa, Billingsley; Lancsar, Emily; McCaffrey, Nicola; Chen, Gang; Gill, Liz; Cameron, Ian D.; Crotty, Maria; Ratcliffe, Julie
Abstract: Consumer directed care (CDC) is currently being embraced internationally as a means to promote autonomy and choice for consumers (people aged 65 and over) receiving community aged care services (CACSs). CDC involves giving CACS clients (consumers and informal carers of consumers) control over how CACSs are administered. However, CDC models have largely developed in the absence of evidence on clients' views and preferences. We explored CACS clients' preferences for a variety of CDC attributes and identified factors that may influence these preferences and potentially inform improved design of future CDC models. Study participants were clients of CACSs delivered by five Australian providers. Using a discrete choice experiment (DCE) approach undertaken in a group setting between June and December 2013, we investigated the relative importance to CACS consumers and informal (family) carers of gradations relating to six salient features of CDC (choice of service provider(s), budget management, saving unused/unspent funds, choice of support/care worker(s), support-worker flexibility and level of contact with service coordinator). The DCE data were analysed using conditional, mixed and generalised logit regression models, accounting for preference and scale heterogeneity. Mean ages for 117 study participants were 80 years (87 consumers) and 74 years (30 informal carers). All participants preferred a CDC approach that allowed them to: save unused funds from a CACS package for future use; have support workers that were flexible in terms of changing activities within their CACS care plan and; choose the support workers that provide their day-to-day CACSs. The CDC attributes found to be important to both consumers and informal carers receiving CACSs will inform the design of future CDC models of service delivery. The DCE approach used in this study has the potential for wide applicability and facilitates the assessment of preferences for elements of potential future aged care service delivery not yet available in policy. Highlights: Australian aged care services increasingly provided as consumer directed care (CDC). Surprisingly, most CDC models do not incorporate aged care service clients' views. This study identified salient features of CDC for consumers and informal carers. Study results can help inform improved design of future CDC models in aged care. DCEs are practical and feasible in populations of dependant consumers.